QUANTUM SPECTRUM ON THE NAKED REISSNER-NORDSTROM BACKGROUND - Gladush, V. D.; Kulikov, D. A. (Одеські астрономічні публікації, 2013)
The eigen frequencies of a massless scalar field in the space-time of the Reissner-Nordstrom singularity are studied by using the WKB approximation and by numerical integration of the wave equation. Both these approaches indicate the existence of long living states for the singularity charge-to-mass ratios being close enough to the extremal value Q/M = 1.